2019
DOI: 10.1159/000495558
|View full text |Cite
|
Sign up to set email alerts
|

Relapsed Philadelphia Chromosome-Positive Pre-B-ALL after CD19-Directed CAR-T Cell Therapy Successfully Treated with Combination of Blinatumomab and Ponatinib

Abstract: Adults with relapsed or refractory (R/R) B-cell acute lymphoblastic leukemia (B-ALL) treated with conventional chemotherapy have dismal outcomes. Novel immunotherapies targeting CD19, including the bispecific T-cell engager blinatumomab and chimeric antigen-receptor T (CAR-T) cells, have revolutionized the treatment of R/R B-ALL. Robust response rates to CAR-T cell therapy after blinatumomab have recently been reported, but it is unknown whether blinatumomab can be effective following failure of anti-CD19 CAR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 24 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Hence, the combination regimen of Ponatinib and Blinatumomab is expected to address the relapse issues after CAR T-cell therapy. El Chaer et al (70) first reported a patient with Ph+ B-ALL who developed CD19-positive relapse after CD19 CAR T-cells treatment and subsequently responded to the combination of blinatumomab and ponatinib, which is a type of TKI and achieved CR for 12 months, indicating that TKI plays a critical role in the induction and maintenance phases of Ph+ B-ALL therapy. This provides a new approach for the prevention of CD19-positive relapse after CAR T-cell therapy.…”
Section: Prevention and Treatment Strategies For Cd19-positive Relapsementioning
confidence: 99%
“…Hence, the combination regimen of Ponatinib and Blinatumomab is expected to address the relapse issues after CAR T-cell therapy. El Chaer et al (70) first reported a patient with Ph+ B-ALL who developed CD19-positive relapse after CD19 CAR T-cells treatment and subsequently responded to the combination of blinatumomab and ponatinib, which is a type of TKI and achieved CR for 12 months, indicating that TKI plays a critical role in the induction and maintenance phases of Ph+ B-ALL therapy. This provides a new approach for the prevention of CD19-positive relapse after CAR T-cell therapy.…”
Section: Prevention and Treatment Strategies For Cd19-positive Relapsementioning
confidence: 99%
“…Multiple clinical trials are underway to evaluate the safety and efficacy of combination of CAR T cells with checkpoint blockade [ 113 , 153 ]. In a separate case report, a patient with Philadelphia chromosome-positive B-ALL, who relapsed after CD19 targeted CAR therapy, was treated with the combination of blinatumomab (bi-specific T cell engagers against CD19 and CD3) and ponatinib (multi-tyrosine kinase inhibitor) [ 115 ]. Remarkably, the patient responded and achieved complete remission lasting 12 months [ 115 ].…”
Section: Types Of Immunotherapy: Their Combinations and Limitationmentioning
confidence: 99%
“…In a separate case report, a patient with Philadelphia chromosome-positive B-ALL, who relapsed after CD19 targeted CAR therapy, was treated with the combination of blinatumomab (bi-specific T cell engagers against CD19 and CD3) and ponatinib (multi-tyrosine kinase inhibitor) [ 115 ]. Remarkably, the patient responded and achieved complete remission lasting 12 months [ 115 ]. It remains to be seen, however, if concurrent combination of these drugs with CAR T cell therapy will result in similar efficacy.…”
Section: Types Of Immunotherapy: Their Combinations and Limitationmentioning
confidence: 99%